Exchange-Traded Funds Investing in the European Emerging Markets - Hilliard, Jitka; Dat Le, Thanh (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
We examine ETFs investing in the equity of emerging European countries. Our sample contains 364 ETFs in developed Europe and 11 emerging European ETFs from 2005 to 2019. Compared to developed Europe’s ETFs, the emerging European equity ETFs are significantly smaller and younger with significantly higher fees. The low correlation of their returns with developed countries and lack of flow sensitivity to the US market volatility suggests that they may be underutilized means of international diversification by investors from developed countries.